Naprężenia w Trójprzegubowym Łuku Tarczowym - K. Wysiatycki (Engineering Transactions, 1958)
The plane state of stress is considered for symmetric plate arches used as bridge structures. The Airy function determining the stresses in the arches is assumed in the form of a series obtained by separating variables in polar coordinates. The integration constants are obtained from a system of linear equations where the coefficients are either ex-pressed in terms of integrals along the contour of the arch or secure the satisfaction of the boundary conditions at n points of the contour. On the circular contour, the boundary conditions in the form of the Airy function or its derivative are satisfied in an accurate manner. An example of numerical calculation is given, together with stress diagrams for two arches.